Characterization of synthesized nickel foam using ammonium hydrogen carbonate as space holder - N.I. Hafiz; M.A. Islam; S. Saha (Results in Engineering)
Nickel foam of cylindrical semi-dense structures is fabricated using powder metallurgy method and ammonium hydrogen carbonate as a space holder. The samples have been obtained after ball milling of both powders and uniaxial compaction of die punch. Then sintering is carried out at 1400 °C for 5 h in an inert atmosphere so that no oxidation could take place. Material characterization has been performed on the prepared three samples of Ni foam having 55 %, 65 % and 75 % of Ni by weight. Subsequent X-ray diffraction and scanning electron microscopy analyses have confirmed the presence of pure Ni and very small amount of oxidation has occurred after the sintering process in Ni -foam. Density and porosity measurements of the fabricated Ni-foams have revealed a range of density from 2.53 g/cc to 5.1 g/cc having an uncertainty below 2.5 % which is quite in acceptable limit while the porosity of the samples varied between 42 % and 71 %, correlating with the concentration of the space holder. Along with that regression analysis between the Ni samples using various machine learning models, XGBoost regression has shown the highest prediction accuracy. Compressive strengths of the samples are in the range from 56.2 MPa to 155 MPa which is inversely proportional to the concentration of the space holder. The obtained results show that the increase in the percentage of metal in Ni foam will increase the strength and density as well as reduce the porosity. However, uniform distribution of porosity and some experimental conditions have been difficult to maintain.